Dynamic Interplay: Seasonal Variation and Growth Stage- Dependent Nutrient Dynamics in Grapevine Physiology and Their Implications for Fruit Quality and Yield Optimisation - Malik, A Roauf; Wani, O. A.; Wani, S.M.; Zargar, R.M.; Manzoor, T.; Ul Haq, S.A.; Shah, H.K. (South African Journal of Enology and Viticulture, 2025)
This study investigated the variation in nutrient content in grape petioles and berries throughout the growing season. Seasonal variation and stage-wise changes in grape fruit yield and quality were correlated with a corresponding nutrient concentration in the plants and berries. The results show that, among medium vines, Perlette exhibited lower plant and fruit characteristics than Anab-e-Shahi. Among the growth stages, the highest was noticed in D9 and the lowest in D1. The study of grapevine development and nutrient dynamics provides a comprehensive understanding of the intricate relationship between vegetative growth and fruit development, offering crucial insights into factors that significantly affect grape quality and yield. The analysis of key parameters such as shoot length, trunk girth, and fruit dimensions, along with the dynamics of fruit weight and number, emphasises the importance of early-season growth and its overarching influence on overall vine productivity. Varietal distinctions, notably between Anab-e-Shahi and Perlette, manifest in unique growth patterns and fruit characteristics. In addition, the investigation delves into the temporal progression of sugar content, identifying a pivotal phase marked by rapid escalation followed by a subsequent decline. The study extends its scope to nutrient dynamics, exemplified by alterations in nitrogen, phosphorus and potassium concentrations in leaf petioles, further enriching the holistic comprehension of grapevine physiology. The cumulative findings offer valuable insights for vineyard management practices aiming to optimise grape quality and yield.